2012
DOI: 10.1136/jmedgenet-2011-100717
|View full text |Cite
|
Sign up to set email alerts
|

NEK1andDYNC2H1are both involved in short rib polydactyly Majewski type but not in Beemer Langer cases

Abstract: This study confirms that NEK1 is one gene causing SRP type II but also reports mutations in DYNC2H1, expanding the phenotypic spectrum of DYNC2H1 mutations. The exclusion of NEK1 and DYNC2H1 in 3/12 SRP type II and in all SRP type IV cases further support genetic heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 10 publications
5
62
0
1
Order By: Relevance
“…These features are reminiscent of the spectrum of SRPII and SRPIV. 1,18,19 Thus, fetuses and individuals reported in this study all display lethal phenotypes consistent with a hedgehogsignaling defect and similar to the phenotype described Mutant Cells (A) KIAA0586 mutant fibroblasts from subject II:2 in family 2 showed an altered response to smoothened agonist (SAG; sc-202814, Santa Cruz; 5 mM for 18 hr), given that they induced less GLI1 and PTCH1 expression than did control cells. Primers used for real-time qRT-PCR are listed in Table S2.…”
supporting
confidence: 60%
“…These features are reminiscent of the spectrum of SRPII and SRPIV. 1,18,19 Thus, fetuses and individuals reported in this study all display lethal phenotypes consistent with a hedgehogsignaling defect and similar to the phenotype described Mutant Cells (A) KIAA0586 mutant fibroblasts from subject II:2 in family 2 showed an altered response to smoothened agonist (SAG; sc-202814, Santa Cruz; 5 mM for 18 hr), given that they induced less GLI1 and PTCH1 expression than did control cells. Primers used for real-time qRT-PCR are listed in Table S2.…”
supporting
confidence: 60%
“…4F) and were also able to exclude cd28 (supplementary material Table S3D). Because mutations in DYNC2H1 cause thoracic dysplasia and ciliary defects in humans (Dagoneau et al, 2009;Merrill et al, 2009;El Hokayem et al, 2012;Schmidts et al, 2013) we first confirmed the nonsense mutation by sequencing single WT and homozygous aa65.6 pd1086 mutant larvae (Fig. 4G).…”
Section: Research Reportmentioning
confidence: 88%
“…The two novel mutations p.A384V and p.Q1451X occur within the highly conserved DHC_N1 and DHC_N2 domains, respectively, which is considered to be the motile element of the dynein heavy chain, directing its movement along the dynein microtubules. Mutations occurring within this region have also been reported to csuse ATD [9,20]. Previous studies suggest that defective DYNC2H1 gene results in disruption of the Hedgehog signaling pathway, affecting the proliferation and differentiation of chondrogenic and osteogenic cells, and finally leads to chondrodysplasia phenotypes [21,22].…”
Section: Discussionmentioning
confidence: 99%